Decentralized Finance and Its Maslahah: Shaping the Future of Financial Services in Indonesia - Amir, Muhammad Fakhri; Kadir, Syahruddin; Sumarlin, Sumarlin (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
Technological innovations are revolutionizing the financial sector through decentralized systems. The emergence of digital currencies necessitates a shift in the financial system toward services that accommodate the development of digital money in the era of Society 5.0. This study aims to explore the potential of Decentralized Finance (DeFi) and its maslahah (benefit) for future financial services in Indonesia. A qualitative approach was employed using library research by collecting primary and secondary data from journals, books, and other literature. Data were analyzed using descriptive analysis through data grouping, data display, and conclusion drawing. The findings indicate that DeFi has the potential to become one of the future financial services as it aligns with technological advancements and the development dimensions of the Society 5.0 era. DeFi offers five maslahah benefits: (1) Protecting religion (hifzu al-din) by serving as an alternative investment instrument; (2) Protecting life (hifzu an-nafs) by becoming a financial market instrument; (3) Protecting progeny (hifzu al-nasl) by encouraging income growth; (4) Protecting intellect (hifzu al-‘aql) by developing human resource potential; and (5) Protecting wealth (hifzu al-maal) by accommodating sources of income and financing for the benefit of society. Therefore, DeFi holds significant potential to contribute positively to Indonesia's financial future by providing services aligned with the values of maslahah and the technological advancements of Society 5.0.========================================================================================================ABSTRAK - Desentralisasi Keuangan dan Maslahahnya: Membentuk Layanan Keuangan Masa Depan di Indonesia. Inovasi teknologi mengarah pada revolusi sektor keuangan melalui sistem terdesentralisasi. Kemunculan mata uang digital memaksa sistem keuangan untuk beralih ke layanan yang mengakomodasi perkembangan uang digital di era 5.0. Penelitian ini bertujuan untuk menggali potensi Decentralized Finance (DeFi) berikut maslahahnya sebagai layanan keuangan masa depan di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan metode kepustakaan, dimana data-data dikumpulkan dari artikel jurnal, buku, dan literatur lainnya. Analisis data dilakukan dengan metode deskriptif melalui pengelompokan data, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa DeFi memiliki potensi untuk menjadi salah satu layanan keuangan di masa depan karena selaras dengan kemajuan teknologi dan dimensi pengembangan untuk era 5.0. DeFi menawarkan lima manfaat maslahah: (1) Melindungi agama (hifzu al-din) dengan menjadi instrumen investasi alternatif; (2) Melindungi jiwa (hifzu an-nafs) dengan menjadi instrumen pasar keuangan; (3) Melindungi keturunan (hifzu al-nasl) dengan mendorong pertumbuhan pendapatan; (4) Melindungi akal (hifzu al-‘aql) dengan mengembangkan potensi sumber daya manusia; dan (5) Melindungi harta (hifzu al-maal) dengan mengakomodasi sumber pendapatan dan pembiayaan untuk kepentingan masyarakat. DeFi memiliki potensi yang signifikan untuk berkontribusi secara positif terhadap masa depan sistem keuangan Indonesia dengan menyediakan layanan yang sejalan dengan nilai-nilai maslahah dan kemajuan teknologi era 5.0.